2024
DOI: 10.3389/fonc.2023.1221616
|View full text |Cite
|
Sign up to set email alerts
|

Screening and surveillance of esophageal cancer by magnifying endoscopy with narrow band imaging improves the survival of hypopharyngeal cancer patients

Chen-Shuan Chung,
Chia-Yun Wu,
Yu-Hsuan Lin
et al.

Abstract: IntroductionPatients with head and neck cancer may develop a second primary neoplasm (SPN) of the esophagus due to field cancerization. This study investigated the impacts of esophageal cancer screening using magnifying endoscopy with narrow-band imaging (ME-NBI) on the outcomes of hypopharyngeal cancer patients.MethodsPatients with hypopharyngeal cancer diagnosed from 2008 to 2021 in a tertiary hospital were reviewed retrospectively. Screening and surveillance using ME-NBI examination of the esophagus were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Yet another issue is that the diagnostic accuracy of NBI has been found to be similar in different upper airway and upper digestive tract locations, assessment types, endoscope systems, as well as in the use of high-definition visualization [ 19 , 20 ]. Thus, NBI may represent a vital additional tool for differentiating between benign and malignant lesions in the nasopharynx [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another issue is that the diagnostic accuracy of NBI has been found to be similar in different upper airway and upper digestive tract locations, assessment types, endoscope systems, as well as in the use of high-definition visualization [ 19 , 20 ]. Thus, NBI may represent a vital additional tool for differentiating between benign and malignant lesions in the nasopharynx [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations for the diagnosis, treatment, and follow-up of NPT in the regions where NPC is endemic, include the use of plasma EBV DNA with a primer/probe assay targeting the BamHI-W region of the EBV genome, performed in duplicate and coupled with endoscopic examination and MRI. This study demonstrated a sensitivity and specificity in screening NPC of 97.1% and 98.6%, respectively [ 20 ]. The recommended endoscopic methods in the abovementioned areas include WLI and NBI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%